Hip Stability Isometric Test (HipSIT): Concurrent Validity and Reference Values for CrossFit® Participants - Thiago R T Santos; Ana Luiza R Rodrigues; Henrique M P Faria; Stéphane M Teixeira; Livia S Pogetti; Andressa Silva; Renan A Resende; Juliana M Ocarino (International Journal of Sports Physical Therapy)
# Background